Wearable human motion tracking and analysis system based on wireless sensor network - Qi, Yongbin (2015)
In this thesis, we first developed a wearable motion tracking system using ultra wideband (UWB) radios, and then a low-cost motion analysis system using wireless ultrasonic sensor network was proposed to overcome the limitations of UWB-based system. The first part of the thesis describes a new method for measuring and monitoring human body joint angles in sagittal plane, which uses wearable ultra wideband (UWB) transceivers mounted on body segments. However, it is difficult to sample the received signals in real time due to its large bandwidth of UWB pulse. This drove us to find some new ways to track human movement. At the second stage of our research, a wearable wireless ultrasonic sensor network was developed to measure the 3-dimensional foot trajectory during walking, and extract some spatial-temporal gait parameters for gait analysis. The proposed ultrasonic motion analysis system uses the wireless sensor network concept with all the mobile nodes communicating wirelessly with the coordinator, enabling patients to be monitored in an unrestrained environment. Based on the measured foot displacements, a methodology has been developed to extract spatial-temporal gait parameters including stride length, stride duration, etc.